2016
DOI: 10.1039/c5dt03875h
|View full text |Cite
|
Sign up to set email alerts
|

A vacuum-annealing strategy for improving near-infrared super long persistent luminescence in Cr3+ doped zinc gallogermanate nanoparticles for bio-imaging

Abstract: Novel Cr(3+) doped zinc gallogermanate (ZGGO) nanoparticles with 697 nm near-infrared (NIR) super long afterglow were prepared via a hydrothermal method. Subsequently, a vacuum-annealing strategy was adopted to improve NIR afterglow in ZGGO:Cr(3+) nanoparticles. For the sample annealed at 800 °C, no variation in the particle size is observed, the persistent luminescence increases by an order of magnitude (∼14 times) and the NIR afterglow time reaches more than 15 hours relative to the as-prepared sample. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 38 publications
4
56
0
Order By: Relevance
“…All tests were performed at room temperature (RT) except for the TL measurements and part of emission spectra. 40 In particular, a slight shi of the (311) peak to lower angles with an increase of Sn 4+ substitution concentration can be observed, as shown in Fig. 1b, further proving that the crystal lattice spacing is increased due to the substitution of Ge 4+ by Sn 4+ .…”
Section: Synthesis and Characterizationmentioning
confidence: 55%
See 1 more Smart Citation
“…All tests were performed at room temperature (RT) except for the TL measurements and part of emission spectra. 40 In particular, a slight shi of the (311) peak to lower angles with an increase of Sn 4+ substitution concentration can be observed, as shown in Fig. 1b, further proving that the crystal lattice spacing is increased due to the substitution of Ge 4+ by Sn 4+ .…”
Section: Synthesis and Characterizationmentioning
confidence: 55%
“…The lifetime of the surface Cr 3+ exhibits a shorter decay time because of Cr 3+ occupying low-symmetry sites. 40 Because the energy level position of the 4 T 2 state is sensitive to the variation in the surroundings of Cr 3+ ions (linearly depends on the variation in the crystal eld strength), we focus on the effect of Sn 4+ substitution on the lifetimes related to the 4 T 2 / 4 A 2 emissions of the surface and interior Cr 3+ . For both the surface and interior Cr 3+ ions, it can be found that the lifetimes of Sn 4+ doped nanoparticles are shorter than those of the undoped nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…According to the above discussion, The enhancement factor F RF can be obtained experimentally by measuring the luminescence intensities, and the life times of τ and τ Ag can be derived through data fitting of the luminescence decay. If we consider the light absorption coefficient α are the same in three samples, and the distribution of Ag NPs are the same at the 14 surface of the particle, then the comprehensive factor of enhanced emission g(ω F ) can be obtained with equation (3). Considering that Ag NPs almost have no influences on UCNPs when the separation layer is 20 nm in thick, one can take g(ω E ) as 1 for the sample S12A.…”
Section: Recalling Thatmentioning
confidence: 98%
“…Lanthanide-doped upconversion nanoparticles(UCNPs) have drawn much attention owing to their applications in biological imaging, solar cells, laser materials and display technologies, etc [1][2][3][4][5][6][7]. However, the fluorescence emission efficiency of UCNPs is not very high due to small absorption coefficient of lanthanide ions [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide-doped upconversion nanoparticles(UCNPs) have attracted much attention owing to their potential applications in biological imaging, solar cell, laser material and display technology [1][2][3][4][5]. However, UCNPs usually have low emission efficiency due to its small absorption coefficient of lanthanide ions [6][7].…”
mentioning
confidence: 99%